A portable high-efficiency electromagnetic energy harvesting system using supercapacitors for renewable energy applications in railroads. (15th June 2016) - Zhang, Xingtian; Zhang, Zutao; Pan, Hongye; Salman, Waleed; Yuan, Yanping; Liu, Yujie
Graphical abstract: In this study, we develop a portable high-efficiency electromagnetic energy harvesting system with supercapacitors that converts the energy of track vibrations into electricity. The generated electricity is stored in the supercapacitors and used in remote areas for safety facilities or in standby power supplies for rail-side equipment. The proposed system consists of a mechanical transmission and a rectifier. Acting as the energy input and transmission, Gears and a rack amplify the small vibrations of the track, and one-way bearings enhance efficiency by transforming bidirectional motion to unidirectional rotation. Supercapacitors are used in the energy harvesting system for the first time. The supercapacitors permit the storage of energy from rapidly changing transient currents and a steady power supply for external loads. The proposed system is demonstrated through dynamic simulations, which show the rapid response of the system. An efficiency of 55.5% is demonstrated in bench tests, verifying that the proposed electromagnetic energy harvesting system is effective and practical in renewable energy applications for railroads. Highlights: A frequently ignored source of energy, railroad track vibrations, is harvested. A novel conversion mechanism is designed to maximize efficiency. Supercapacitors are included in the electromagnetic energy harvesting system. A portable design is proposed for wider application. Abstract: As the demand for alternative sources of energy has increased, harvesting abundant environmental energy such as vibration energy including track vibrations in railway systems has attracted greater attention. In this study, we develop a portable high-efficiency electromagnetic energy harvesting system with supercapacitors that converts the energy of track vibrations into electricity. The generated electricity is stored in the supercapacitors and used in remote areas for safety facilities or in standby power supplies for rail-side equipment. The proposed system consists of a mechanical transmission and a regulating circuit. Acting as the energy input and transmission, Gears and a rack amplify the small vibrations of the track, and one-way bearings enhance efficiency by transforming bidirectional motion to unidirectional rotation. Supercapacitors are used in the vibration energy harvesting system for the first time. The supercapacitors permit the storage of energy from rapidly changing transient currents and a steady power supply for external loads. The proposed system is demonstrated through dynamic simulations, which show the rapid response of the system. An efficiency of 55.5% is demonstrated in bench tests, verifying that the proposed electromagnetic energy harvesting system is effective and practical in renewable energy applications for railroads.